Greenland‐Wide Seasonal Temperatures During the Last Deglaciation. Issue 4 (19th February 2018) - Buizert, C.; Keisling, B. A.; Box, J. E.; He, F.; Carlson, A. E.; Sinclair, G.; DeConto, R. M.
Abstract: The sensitivity of the Greenland ice sheet to climate forcing is of key importance in assessing its contribution to past and future sea level rise. Surface mass loss occurs during summer, and accounting for temperature seasonality is critical in simulating ice sheet evolution and in interpreting glacial landforms and chronologies. Ice core records constrain the timing and magnitude of climate change but are largely limited to annual mean estimates from the ice sheet interior. Here we merge ice core reconstructions with transient climate model simulations to generate Greenland‐wide and seasonally resolved surface air temperature fields during the last deglaciation. Greenland summer temperatures peak in the early Holocene, consistent with records of ice core melt layers. We perform deglacial Greenland ice sheet model simulations to demonstrate that accounting for realistic temperature seasonality decreases simulated glacial ice volume, expedites the deglacial margin retreat, mutes the impact of abrupt climate warming, and gives rise to a clear Holocene ice volume minimum. Plain Language Summary: The Greenland ice sheet could contribute 7 m (23 feet) of sea level rise if it were to melt completely. For future sea level rise predictions we need to know how the Greenland ice sheet will respond to rising temperatures. We can figure out how sensitive Greenland is by studying a natural period of warming (called the last deglaciation) that happened at the end of the last Ice Age 18, 000 years ago. During the last Ice Age the Greenland ice sheet was much larger than it is today, and as the climate warmed it shrunk to its present size. We combine ice core data and climate models to reconstruct Greenland‐wide temperatures for all seasons over the last 22, 000 years. This reconstruction makes it possible to simulate Greenland ice loss during the last deglaciation in ice sheet models. The model output can be compared to data on past ice sheet volume, for example, from moraines left behind in the landscape as the ice melted. Our reconstruction provides a critical step in learning from the past behavior of the Greenland ice sheet in order to predict its future. Key Points: Merging climate models and ice core data gives seasonality and spatial pattern of deglacial warming Temperature fields are useful for forcing ice sheet models and interpreting local ice retreat Temperature seasonality expedites deglacial ice loss and mutes the impact of abrupt climate change